Comparison of high-frequency transabdominal ultrasonography and spiral computed tomography with colonoscopy in diagnosis of colon cancer - Sumnyan, Wangju; Komut, Ojing; Ligu, Leena (International Journal of Medical Research and Review, 2018)
Objective: To compare high-frequency transabdominal ultrasonography (USG) and spiral computed tomography (CT) with colonoscopy in diagnosis of colon cancer. Design: A prospective comparative study of accuracy of USG and CT scan with colonoscopy. Subjects: Sixty patients with a clinical suspicion of colon cancer after a detailed clinical history and a thorough clinical examination were included. Patients with a known diagnosis of colon cancer or in whom histopathological diagnosis could not be established were excluded. Methods: All 60 patients who met the inclusion and exclusion criteria underwent transabdominal USG, CT scan-abdomen & pelvis, followed by colonoscopy. The CT and USG scans were reported by different radiologists without previous knowledge of any findingsof the other test or of the subsequent colonoscopy. The colonoscopy was performed by different clinicians, none of whom was aware of the USG or CT diagnosis. Result: Colonoscopy diagnosed 29 patients with colon cancer out of 60 enrolled patients. USG detected colon cancer in all the 29 patients with a sensitivity of 100% and a specificity of 87.1%. CT scan diagnosed colon cancer in all the 29 patients with a sensitivity of 100% and a specificity of 74.2%. Conclusions: Colonoscopy is still necessary when a suspicious lesion is identified. However, CT and USG can screen out suspected patients who can be subsequently referred for colonoscopy. This would reduce the need for colonoscopy in a large proportion of clinically suspected patients andalso avoidan invasive procedure like colonoscopy as first line investigation in elderly patients suspected of having colonic cancer.